Review paperDermatological problems of the puberty - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Puberty is a period of life between childhood and adulthood. It is characterized by many changes in morphology and appearance of the body (biological maturation), in the psyche – development of personality (psychological maturation), and in the attitude towards one’s own and the opposite sex (psychosexual maturation), and in the social role (social maturation). Dermatological problems of adolescence are mainly related to fluctuations in hormone levels, mainly androgens. They include acne, hair problems and excessive sweating. Acne vulgaris is the most frequently diagnosed dermatosis in patients aged between 11 and 30 years. It is believed that it affects about 80% of persons in this age group or even, taking into account lesions of low intensity, 100% of young people. Excessive sweating is a condition characterised by excessive production of sweat, resulting from high activity of sweat glands. The sweat glands are localised in almost all areas of the body surface but on the hands, feet, armpits and around the groin they are found at the highest density. Seborrhoeic dermatitis of the scalp is a chronic, relapsing, inflammatory dermatosis, which currently affects about 5% of the population. It affects mostly young people, particularly men.